2016
DOI: 10.1590/0004-282x20160163
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder and drug addiction rehabilitation patients

Abstract: Attention deficit hyperactivity disorder (ADHD) manifests as a behavioral pattern that leads to significant social, educational and occupational impairment. The main characteristics of the disorder are inattention, hyperactivity and impulsivity 1. The diagnosis of ADHD is clinical and is based on a persistent, early-onset clinical picture that manifests in different settings and leads to functional loss 2 . A failure in behavioral inhibition is believed to lead to the predominant symptoms of ADHD: hyperactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…The results showed that early cannabis exposure plays a central role in later substance use. The figures are robust enough to support its important conclusion, reinforcing the findings of Camargo and colleagues 3 .…”
supporting
confidence: 85%
“…The results showed that early cannabis exposure plays a central role in later substance use. The figures are robust enough to support its important conclusion, reinforcing the findings of Camargo and colleagues 3 .…”
supporting
confidence: 85%
“…Here, the age of first cocaine use was lower among the ADHD population than other groups undergoing rehab. ADHD patients in rehab overrepresented ADHD patients found in the general population [15]. Age of first use for cannabis correlated with age of facility admission, as well as frequency of ADHD symptoms.…”
Section: How Does Cannabis Act As a Gateway Drug?mentioning
confidence: 83%
“…They also looked at the likelihood of subsequent cocaine use and severity of dependence. One central premise to this and other ADHD drug dependence studies is that there is a failure of behavioral inhibition that leads to hyperactivity, inattention, distraction and impulsivity [15]. Investigators found that cocaine dependence was greater than that of cannabis.…”
Section: How Does Cannabis Act As a Gateway Drug?mentioning
confidence: 99%
“…Another study on British prisoners, on the contrary, show that combined ADHD type is significantly associated with the need for coping as a way of managing primary and comorbid symptoms, but not conduct disorder [36]. Brazilian study also found no difference in drug use or dependence prevalence between ADHD and non-ADHD patients but observed different addiction patterns such as earlier use of cocaine and more severe use of cocaine correlated to earlier contact with cannabis [37]. The longitudinal study followed participants with childhood-limited ADHD and persistent ADHD compared to controls and found that there were no significant group differences in change in rates of substance dependence over time.…”
Section: Prevalence and Symptom Severitymentioning
confidence: 95%